2017
DOI: 10.1016/j.ejso.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the future remnant liver function is a better tool to predict post-hepatectomy liver failure than platelet-based liver scores

Abstract: eFLRF is a better predictor of PHLF than PBLS or HBS alone. PBLS seem to measure other aspects of liver function or damage than HBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Moreover HBS takes into account the possible heterogeneity of the distribution of function within liver. HBS is also better than platelet-based liver scores in predicting PHLF (15)(16)(17). de Graaf et al showed that a cutoff of 2.7%/min/m 2 is of high negative predictive value (98%) to exclude the risk of PHLF in patients planned for large hepatectomy (10) (Figure 1).…”
Section: Review Articlementioning
confidence: 99%
“…Moreover HBS takes into account the possible heterogeneity of the distribution of function within liver. HBS is also better than platelet-based liver scores in predicting PHLF (15)(16)(17). de Graaf et al showed that a cutoff of 2.7%/min/m 2 is of high negative predictive value (98%) to exclude the risk of PHLF in patients planned for large hepatectomy (10) (Figure 1).…”
Section: Review Articlementioning
confidence: 99%
“…The resection of large liver tumors is a frequent intractable problem for liver surgeons (1). A larger hepatectomy can lead to serious complications, including post-hepatectomy liver failure and small-for-size syndrome (2,3). Portal vein ligation (PVL) (4) or portal vein embolization (PVE) (5) have been widely used to increase the future liver volume (FLV) and reduce complication risk of patients with marginal FLVs.…”
Section: Introductionmentioning
confidence: 99%
“…The median number of included patients undergoing both a preprocedural nuclear medicine imaging examination and a procedure with the purpose of eliminating diseased liver tissue was 67 (5 to 625 patients). Some studies investigated major surgery exclusively including some studies investigating associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) [ 21 , 69 , 72 , 80 , 82 , 83 ]. The majority of the studies investigated both major and minor surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve of these trials presented the predictive impact with an OR or HR. Eleven of these studies tested other variables as well, and only six of these studies [21,22,36,57,64,65] found that other variables (e.g., operation time, extent of hepatectomy, blood loss volume, and aspartate aminotransferase to platelet ratio index) had significant predictive value for predicting LF.…”
Section: Prediction Of Postoperative Lfmentioning
confidence: 99%